Guidelines for Digital Twins in 5g Agriculture - Soto-Gomez, J; Zamorano-Illanes, R (Institute of Electrical and Electronics Engineers Inc., 2022)
New devices for the Internet of Things (IoT) and 5G enable monitoring and controlling of environments and objects in agriculture and other areas. Digital Twins is a growing concept connecting IoT with applications to automate agriculture, predicting crop behavior through data analysis. However, there is a conceptual gap between the digital twin concept and its application to real development. This work proposes a novel meta classes model to guide designs on digital twins in agriculture based on a bibliometric analysis to identify the current works in the area. The proposed design considers several meta classes such as communication devices, sensors, actuators, historical sensing, visualization, Human-Machine Interfaces, decisions, physical objects, and physical sectors. These meta-classes can work on a Jetson nano processor or a Raspberry Pi because they can be implemented in several languages and frameworks. © 2022 IEEE.